2022
DOI: 10.3389/fphar.2022.866738
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Scavenging as a Neuroreparative Strategy in Ischemic Stroke

Abstract: Stroke is the second highest reason of death in the world and the leading cause of disability. The ischemic stroke makes up the majority of stroke cases that occur due to the blockage of blood vessels. Therapeutic applications for ischemic stroke include thrombolytic treatments that are in limited usage and only applicable to less than 10% of the total stroke patients, but there are promising new approaches. The main cause of ischemic neuronal death is glutamate excitotoxicity. There have been multiple studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…With ATP depletion, the Ca 2+ cannot be pumped out of neuron cells and causes glutamate release ( Luoma et al, 2011 ). Postsynaptic receptors of glutamate include ionotropic receptors or metabotropic receptors (mGluRs), the ionotropic type receptor, NMDA (N-methyl-D-aspartate) receptor, which primarily regulates the excitotoxic response ( Kaplan-Arabaci et al, 2022 ). Overactivation of glutamate receptors leads to the opening of receptor-gated calcium channels and Ca 2+ influx, and the increase of intracellular Ca 2+ causes a series of pathological reactions in the cytoplasm and nucleus ( Lai et al, 2014 ).…”
Section: Pathophysiologies Of Ischemic Strokementioning
confidence: 99%
“…With ATP depletion, the Ca 2+ cannot be pumped out of neuron cells and causes glutamate release ( Luoma et al, 2011 ). Postsynaptic receptors of glutamate include ionotropic receptors or metabotropic receptors (mGluRs), the ionotropic type receptor, NMDA (N-methyl-D-aspartate) receptor, which primarily regulates the excitotoxic response ( Kaplan-Arabaci et al, 2022 ). Overactivation of glutamate receptors leads to the opening of receptor-gated calcium channels and Ca 2+ influx, and the increase of intracellular Ca 2+ causes a series of pathological reactions in the cytoplasm and nucleus ( Lai et al, 2014 ).…”
Section: Pathophysiologies Of Ischemic Strokementioning
confidence: 99%
“…Using an animal model of MCAO, Campos et al showed that activation of glutamate oxaloacetate transaminase inhibits the increase in glutamate after cerebral ischemia ( 40 ). Infarct size, edema volume, and sensorimotor deficits are significantly reduced as a result of the activation of glutamate oxaloacetate transaminase ( 40 , 41 ). Fang et al examined the effects of histamine on expression of glutamate transporter-1 (GLT-1) in an adult rat model of MCAO and found that inhibition of GLT-1 expression reduces excitatory toxicity ( 42 ).…”
Section: Molecular Pathological Hallmarks Of Ischemic Strokementioning
confidence: 99%
“…One of the critical events following cerebral ischemia is that Na + -K + -ATPase activity decreases when intracellular ATP drops below 25% of normal levels. This results in the massive inward flow of sodium, outward flow of potassium, severe disruption of intracellular ion homeostasis, and presynaptic membrane depolarization [18,31]. Subsequently, a large number of neurotransmitters, including glutamate, are released into the synaptic gap [32].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…After approximately 4.5 h, the risk of death due to intracranial hemorrhage induced by intravenous tPA administration increases by 5%, far exceeding the possible benefits [15][16][17]. Owing to this narrow time window and the contraindications to thrombolysis, tPA therapy is only suitable for fewer than 10% of stroke patients [18,19]. Therefore, there is an urgent need to devise alternative strategies for rescuing ischemic brain tissue.…”
Section: Introductionmentioning
confidence: 99%